Framework Administered Account for Selected Fund Activities : Financial Access Survey Subaccount. (Policy Papers; Policy Paper ;, 2013)
In March 2009 the Fund established a new Framework Administered Account to administer external financial resources for Selected Fund Activities (the 'SFA Instrument'). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of subaccounts within the SFA. This paper requests Executive Board approval to establish the Financial Access Survey Subaccount ('the Subaccount') under the terms of the SFA Instrument.